The quirks of digital culture - Beer, David, 1977- (Emerald Publishing Limited, 2019)
This book explores the quirks of digital culture. Through a series of short punchy chapters, it uses these quirks as momentary glimpses into the hidden dynamics of our swirling, highly mediated and often unfathomable cultural experiences. -- Provided by publisher